Pendampingan dan Pemenuhan Lampu Panel Surya Sebagai Penerangan Area Taman dalam Konsep Lingkungan Berkelanjutan Bagi Warga - Putra, Heristama Anugerah; Kristianto, Ryan Putranda; Andrian, David; Oktaviani, Yohana Christela; Subhagia, Andreas Andika Putra (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2024)
Large and excessive use of electricity, especially for lighting, is also a problem in itself, namely the large expenditure on electricity bills. For this reason, the public is encouraged to use energy-saving lighting such as LED lights or the use of solar panels. Residents want sufficient lighting in public facility areas. Community service activities are carried out at the Babatan Pilang RT Housing Complex. 002 RW. 005, where residents expect assistance from the team to provide education on effective ways to overcome large electricity costs in order to save energy. Apart from that, it will also be realized in the physical form of installing garden lights based on the use of solar panels to remain energy efficient. So that from the results of counseling and fulfillment of garden lights, residents can understand and understand how to save money by getting to know the types of energy-saving lights such as solar panel lights. In terms of park functions, solar panel lights can be shared by residents even if they are used at night.